Identifying HIV infection in South African women: How does a fourth generation HIV rapid test perform? - Kapila Bhowan (African Journal of Laboratory Medicine, 2011)
Background: HIV rapid tests (RT) play an important role in tackling the HIV pandemic in South Africa. Third generation RT that detect HIV antibodies are currently used to diagnose HIV infection at the point of care. Determine Combo (DC) is the first fourth generation RT that detects both p24 antigen (p24Ag) and HIV antibodies (Ab), theoretically reducing the window period and increasing detection rates. Early detection of maternal HIV infection is important to mitigate the high risk of vertical transmission associated with acute maternal infection. Objectives: We assessed the performance of the DC RT against third generation RT in antenatal and post-partum women. Methods: Third generation RT Advance Quality and Acon were used in a serial algorithm to diagnose HIV infection in antenatal and post-partum women over six months at a tertiary hospital in Johannesburg, South Africa. This data provided the reference against which the DC RT was compared on plasma and whole blood samples. Results: The 1019 participants comprised 345 (34%) antenatal and 674 (66%) post-partum women. Ninety women (8.8%) tested HIV-positive of whom 59 (66%) were tested antenatally, and 31 (34%) post-partum yielding prevalence rates of 17.1% and 4.6% respectively. The sensitivity and specificity of the Ab component of DC on plasma antenatally was 100% (93.8% – 100%) and 100% (98.6% – 100%) respectively and post-partum was 100% (88.9% – 100%) and 99.6% (98.8% – 99.9%) respectively. One false positive and not a single true positive p24Ag was detected. Of 505 post-partum women who tested HIV-negative 6–12 months prior to enrolment, 12 (2.4%) seroconverted. Conclusion: The fourth generation DC offered no advantage over current third generation RT in the diagnosis of HIV infection.